Challenges of short substrate analogues as SARS-CoV-2 main protease inhibitors. (15th October 2021) - Ullrich, Sven; Sasi, Vishnu M.; Mahawaththa, Mithun C.; Ekanayake, Kasuni B.; Morewood, Richard; George, Josemon; Shuttleworth, Laura; Zhang, Xiaobai; Whitefield, Cassidy; Otting, Gottfried; Jackson, Colin; Nitsche, Christoph
Graphical abstract: Abstract: Specific anti-coronaviral drugs complementing available vaccines are urgently needed to fight the COVID-19 pandemic. Given its high conservation across the betacoronavirus genus and dissimilarity to human proteases, the SARS-CoV-2 main protease (M pro ) is an attractive drug target. SARS-CoV-2 M pro inhibitors have been developed at unprecedented speed, most of them being substrate-derived peptidomimetics with cysteine-modifying warheads. In this study, M pro has proven resistant towards the identification of high-affinity short substrate-derived peptides and peptidomimetics without warheads. 20 cyclic and linear substrate analogues bearing natural and unnatural residues, which were predicted by computational modelling to bind with high affinity and designed to establish structure–activity relationships, displayed no inhibitory activity at concentrations as high as 100 μM. Only a long linear peptide covering residues P6 to P5 ′ displayed moderate inhibition ( K i  = 57 µM). Our detailed findings will inform current and future drug discovery campaigns targeting M pro .